Acute myocardial infarction in a Chinese patient with paroxysmal nocturnal hemoglobinuria: A case report. Issue 33 (August 2019) - Li, Gang; Hu, Rui; Gao, Yifang
Abstract: Rationale: Paroxysmal nocturnal hemoglobinuria (PNH) is a clonal hematopoietic stem cell disease. Patients with PNH often experience a high incidence (14%–40%) of thrombotic events, which are mainly venous and rarely arterial thrombotic events. Because it is very rare, delay in diagnosis is common in patients with PNH, imposing a remarkable impact on patient's management and prognosis. Patient concerns: We presented a 33-year-old female case with no medical history of any systemic illnesses who complained of approximately 1-month progressively worsening constant heartburn, and was also hospitalized twice due to acute myocardial infarction (AMI). Diagnoses: In our case, AMI occurred twice, whereas there were no cardiovascular risk factors and abnormalities based on the angiography of the coronary artery. Flow cytometry analysis showed that 25% of CD55 and CD59 were lost on the surface of neutrophils, and 30% of CD55 and CD59 were lost on the surface of the blood cells. Thus, our diagnosis of this patient was AMI secondary to PNH. Interventions and outcomes: For the first myocardial infarction, local hospitals used thrombolytic therapy to alleviate symptoms. After the patient's second myocardial infarction was treated in our hospital, we adopted coronary interventional therapy. Considering the patient's situation, eculizumab was given for treatment. The patient was gradually restored to achieve stability, and the follow-up observation showed that there was no arterial thrombosis. Lessons: This case report aimed to provide a reliable reference for the rare cause of AMI. In addition, PNH should be highly taken into consideration in young patients who have a rare cause of AMI.